Lead extractions in patients with cardiac implantable electronic device infections: Single center experience. Issue 4 (22nd March 2016) - Goya, Masahiko; Nagashima, Michio; Hiroshima, Ken‐ichi; Hayashi, Kentaro; Makihara, Yu; Fukunaga, Masato; An, Yoshimori; Ohe, Masatsugu; Yamazato, So‐ichiro; Sonoda, Ko‐ichiro; Yamashita, Kennosuke; Katayama, Kouji; et al.
Abstract: Background: Lead extraction using laser sheaths is performed mainly for cardiac implantable electronic device (CIED) infections. However, there are few reports concerning the management of CIED infections in Japan. Methods and results: Lead extraction procedures were performed in 183 patients targeting 450 leads (atrial leads: 170, ventricular: 181, implantable cardioverter‐defibrillators (ICDs): 79, and coronary sinus: 20). One hundred twenty patients (65.6%) presented with pocket infections without the presentation of an endovascular infection. Blood cultures were positive at least once in 63 patients (34.4%). Complete procedure success was achieved for 437 leads (97.1%) while partial removal occurred in nine, and failure in four leads. Major complications directly related to the procedure occurred in five patients (2.7%). Two of the four patients with a cardiac tamponade required a surgical repair. All patients received intravenous antibiotics, at least, one week after the procedure. Pocket or systemic infections were successfully controlled in 181 patients (98.9%). Coagulase‐negative staphylococci (30.1%) and Staphylococcus aureus (37.1%) were the most common causes of CIED infections. Conclusion: The current status of CIED infections in Japan seems to be similar to that previously reported from foreign countries. The optimal treatment of CIED infections involves the complete explantation of all hardware, followed by antibiotic therapy.